2018
DOI: 10.1111/ijau.12136
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of audit report lag: A meta‐analysis

Abstract: This paper provides a meta‐analysis of the determinants of audit report lag, defined as the period between a company's fiscal year end and the audit report date. We group the meta‐analyzed studies into three categories: (a) audit and audit‐related determinants, (b) corporate governance‐related determinants, and (c) firm‐specific determinants. We find that audit opinion and audit season variables increase audit report lag, whereas Big 4 affiliation, nonaudit services, and auditor tenure decrease audit report la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
127
3
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(186 citation statements)
references
References 155 publications
18
127
3
10
Order By: Relevance
“…The result of the study consistent with studies of Khasharmeh and Aljifri (2010) and Fujianti and Satria (2020). Whereas the study results contrary with the studies of Lee and Jahng (2008), Ahmed and Hossain, (2010), Mazkiyani and Handoyo (2017), and Habib, Bhuiyan, Huang and Miah (2019).…”
Section: Correlation Analysissupporting
confidence: 86%
“…The result of the study consistent with studies of Khasharmeh and Aljifri (2010) and Fujianti and Satria (2020). Whereas the study results contrary with the studies of Lee and Jahng (2008), Ahmed and Hossain, (2010), Mazkiyani and Handoyo (2017), and Habib, Bhuiyan, Huang and Miah (2019).…”
Section: Correlation Analysissupporting
confidence: 86%
“…By examining the CEO's characteristics association with audit report lag, this study contributes to the growing literature of board diversity, including gender diversity (Goodstein et al, 1994;Byrne et al, 2005;Ferreira, 2010;Harjoto et al, 2015), corporate governance (Manner, 2010;Kaplan, Klebanov, & Sorensen, 2012;Mitra et al, 2012;Uygur, 2018) and audit research specifically, audit report lag (Schwartz & Soo, 1996;Knechel & Payne, 2001;Blankley et al, 2015;Habib et al, 2019). With an increase awareness on board diversity and gender diversity, it is expected that the data of interest will becoming richer and board dynamic will be a fertile area for future corporate governance and audit research.…”
Section: Resultsmentioning
confidence: 93%
“…Not only that it is more stable measure, it also acts as performance matching for sample firms (Kothari, Leone, & Wasley, 2005). Prior research finds that on average, profitability is likely to have positive effect on audit report lag (Habib, Bhuiyan, Huang, & Miah, 2019). In contrast, evidence from prior research indicates that financial loss and complexity of the firm tend to increase audit report lag (Bamber et al, 1993).…”
Section: Control Variablesmentioning
confidence: 99%
“…It has been shown that SIZE, reflecting the complexity of a company, increases audit effort and hence ARL (Gros et al, 2017;Knechel & Sharma, 2012). Likewise, COWN, LEV, and PROF, indicating the company's financial situation, can negatively affect ARL (e.g., Habib, Bhuiyan, Huang, & Miah, 2019;Wan-Hussin. & Bamahros, 2013).…”
Section: Control Variablesmentioning
confidence: 99%